2016
DOI: 10.1007/s00216-015-9266-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method based on ultra high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry for studying the in vitro metabolism of phosphorothioate oligonucleotides

Abstract: Ultra high performance liquid chromatography hyphenated with quadrupole time-of-flight mass spectrometry was used to determine the products of the in vitro metabolism of phosphorothioate oligonucleotides. These compounds may be used during antisense therapy as synthetic fragments of genes. For this reason, both a sample preparation method and a qualification method were developed during this study. Liquid–liquid extraction, protein or oligonucleotide precipitation, and solid-phase extraction were tested and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 17 publications
(25 reference statements)
3
32
0
Order By: Relevance
“…However, the results interestingly showed that the absence of NADPH, an enzyme cofactor for CYP450/FMO, resulted in the absence of metabolism in unmodified oligonucleotides, implying that NADPH is required to generate typical chain‐shortened metabolites for oligonucleotides. In addition, there was no difference between using 3 and 6 m m NADPH, which was consistent with findings from a previous study (Studzińska et al, 2016). Finally, the oligonucleotide samples were incubated in a buffer consisting of 100 m m Tris–HCl (pH 8.0), 1 m m magnesium acetate, 1× penicillin/streptomycin, and 3 m m NADPH.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, the results interestingly showed that the absence of NADPH, an enzyme cofactor for CYP450/FMO, resulted in the absence of metabolism in unmodified oligonucleotides, implying that NADPH is required to generate typical chain‐shortened metabolites for oligonucleotides. In addition, there was no difference between using 3 and 6 m m NADPH, which was consistent with findings from a previous study (Studzińska et al, 2016). Finally, the oligonucleotide samples were incubated in a buffer consisting of 100 m m Tris–HCl (pH 8.0), 1 m m magnesium acetate, 1× penicillin/streptomycin, and 3 m m NADPH.…”
Section: Resultssupporting
confidence: 92%
“…The in vitro incubation with endo/exonucleases (DNase I and Exonuclease I) and mouse liver homogenates was performed according to the manufacturer's protocol and our previous optimized conditions. Along with the in vitro endo/exonucleases and mouse liver homogenates, the incubation with human liver microsome (HLM) has been applied to test the metabolic stability of oligonucleotides (Studzińska et al, 2016). Based on the previous information from available literature (Studzińska et al, 2016; Zou, Tiller, Chen, Beverly, & Hochman, 2008) and manufacturer protocol provided by BD Biosciences (San Jose, CA, USA), the process to modify the conditions with HLM included the concentrations of HLM (0.5 or 1 mg/mL) and NADPH (0, 3, or 6 m m ), and the reaction buffer (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The [M − H] − of this signal was 345 Da smaller than that of LNA‐A, and its mass suggested that deoxyguanosine thiophosphate at the 3′ end had been removed from LNA‐A. Studzińska et al reported that antisense oligonucleotides are metabolized from the 3′ end in in vitro experiments using human liver microsomes . Furthermore, the ion with m/z 4614, probably generated by a biological reaction, was not detected in the homogenate section (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…These unresolved impurities preclude an accurate measure of assay based on chromatographic separation alone. The increased resolving power of UPLC chromatography that has been utilized to distinguish different sequences or metabolites of phosphorothioate oligonucleotides is not helpful in this situation, since the inability to separate impurities from API is due the retention time distribution of stereoisomers rather than insufficient chromatographic resolution. As a result, increasing the resolution of the IP‐HPLC method leads to separation of the stereoisomers comprising the API and broadening of the main peak rather than improved separation of impurities.…”
Section: Introductionmentioning
confidence: 99%